Neurobiological consequences of traumatic brain injury - McAllister, Thomas W. (Les Laboratoires Servier, 2011)
Traumatic brain injury (TBI) is a worldwide public health problem typically caused by contact and inertial forces acting on the brain. Recent attention has also focused on the mechanisms of injury associated with exposure to blast events or explosions. Advances in the understanding of the neuropathophysiology of TBI suggest that these forces initiate an elaborate and complex array of cellular and subcellular events related to alterations in Ca(++) homeostasis and signaling. Furthermore, there is a fairly predictable profile of brain regions that are impacted by neurotrauma and the related events. This profile of brain damage accurately predicts the acute and chronic sequelae that TBI survivors suffer from, although there is enough variation to suggest that individual differences such as genetic polymorphisms and factors governing resiliency play a role in modulating outcome. This paper reviews our current understanding of the neuropathophysiology of TBI and how this relates to the common clinical presentation of neurobehavioral difficulties seen after an injury.